2012
DOI: 10.1149/2.030301jes
|View full text |Cite
|
Sign up to set email alerts
|

Indium Tin Oxide Electrode Modified by a NH2+Ion Implantation Technique for Determination of Daunorubicin

Abstract: The effect of surface modification of Indium tin oxide by a NH2+ ion implantation technique has been studied to detect daunorubicin, an anticancer drug. The current was linearly dependent on the scan rate, indicating that the direct electrochemistry of daunorubicin in that case was a surface-controlled electrode process. The NH2/ITO electrode successfully detected the reduction signals of daunorubicin in the linear range of 1.0 × 10−9∼3.0 × 10−6 M and the detection limit was 2.0 × 10−10 M (at S/N = 3). NH2/ITO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The XPS spectra for bare ITO and NH 2 /ITO electrodes were published in the literature [28], which were used to confirm the successful formation of NÀH bonds. The XPS spectra in the N 1s region showed a much higher asymmetric peak than that of bare ITO at 399.9 eV, which was attributed to NH 2 groups, suggesting that NH 2 groups were modified on ITO surface.…”
Section: Characterization Of Nh 2 /Ito Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…The XPS spectra for bare ITO and NH 2 /ITO electrodes were published in the literature [28], which were used to confirm the successful formation of NÀH bonds. The XPS spectra in the N 1s region showed a much higher asymmetric peak than that of bare ITO at 399.9 eV, which was attributed to NH 2 groups, suggesting that NH 2 groups were modified on ITO surface.…”
Section: Characterization Of Nh 2 /Ito Electrodementioning
confidence: 99%
“…Atomic force microscope experiments could furnish the morphological characteristic information about the surface of ITO film. AFM images of bare ITO electrode and NH 2 /ITO electrode were published in literature [28], which illustrated the three dimensional view of the tapping mode image of the bare ITO film (A) and NH 2 /ITO film (B). From the measurements, the surface roughness of the NH 2 /ITO film (2.83 nm) is more than that of the bare ITO film (1.72 nm), which conformed the morphological change of the ITO film after ion implantation.…”
Section: Characterization Of Nh 2 /Ito Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the types of electrolytes, Li-air batteries can be divided into four categories: aprotic [2,3], aqueous [4], solid state [5] and mixed aqueous/aprotic [6,7]. Rapid development of Li-air battery in the past decade resulted in quite a number of sinificant publications on all aspects of Li-air battery, including anode [8], cathode [9,10], electrolyte [11] and overall review [12].…”
Section: Introductionmentioning
confidence: 99%
“…M-30 is mostly constituted by micro-size pores and macro-/meso-pores which can easily block oxygen diffusion when filled with liquid electrolyte. In addition, these two kinds of pores can also be easily blocked by precipitation of reaction products (such as Li 2 O 2 ) [9,18]. Thus, it can be concluded that the majority of the specific capacity is contributed by inter-particle pores.…”
mentioning
confidence: 99%